PENGARUH RETURN ON ASSETS (ROA) DAN CURRENT RATIO (CR) TERHADAP CASH EFFECTIVE TAX RATE (CETR) PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Putri, Maritza Zahwa Arinditya; Mudzakir, Ahmad; Suhendi, Suhendi (LP2M Universitas Bina Bangsa, 2024)
Taxation is one of the most important sources of funding for Indonesia, where income from taxes will be allocated for infrastructure development and public services. Taxes can have a big impact on government income and state budget budgeting, the Indonesian government has made various tax policies and regulations to maximize tax department income. This is because companies as taxpayers indicate tax as a burden that they want to avoid because they can reduce the company's net profit. The difference in interests between the government and the taxpayer leads to tax avoidance or tax avoidance by the taxpayer in the form of exploiting tax law loopholes. This article aims to test the effect of Return on Asset and Current Ratio on the Cash Effective Tax Rate on PT Harum Energy Tbk. ROA is the company's profit-making capability. Meanwhile, CR is the company's ability to pay off its obligations smoothly. This article uses descriptive methods and quantitative approaches. The data in this article is secondary data taken from the financial statements of PT Harum Energy, Tbk and supported by library and documentation studies processed statistically and quantitatively. The results of this study concluded that partial Return on Assets and Current Ratio had a negative and insignificant effect on the Cash Effective Tax Rate. Simultaneously ROA and CR have no significant effect on CETR. The contribution of these two variables was only 37.4% meaning that 62.6% of CETR was influenced by other factors outside this study